Wearable UV Meter – An EPS@ISEP 2017 Project - Lönnqvist, Elin (2018)
This paper reports the collaborative design and development of Helios, a wearable UltraViolet (UV) meter. Helios is intended to help preventing the negative effects of over-exposure to UV radiation, e.g., sun burning, photo ageing, eye damage and skin cancer, as well as of under-exposure to solar radiation, e.g., the risk of developing vitamin D shortage. This project-based learning experience involved five Erasmus students who participated in EPS@ISEP – the European Project Semester (EPS) at Instituto Superior de Engenharia do Porto (ISEP) – in the spring of 2017. The Team, motivated by the desire to find a solution to this problem, conducted multiple studies, including scientific, technical, sustainability, marketing, ethics and deontology analyses, and discussions to derive the requirements, design structure, functional system and list of materials and components. The result is Helios, a prototype Wearable UV Meter that can be worn as both a bracelet and a clip-on. The tangible result was the Helios prototype, but more importantly was the learning experience of the Team, as concluded from their closing statements.